The crystal structure of 1H-benzimidazole-2-carboxamide, C8H7N3O - Ma Hang; Tian Qiang; Wan Banglong (Zeitschrift für Kristallographie - New Crystal Structures)
C8H7N3O, orthorhombic, Pccn (no. 56), a = 9.9071(14) Å, b = 11.1950(19) Å, c = 13.315(2) Å, V = 1476.8(4) Å3, Z = 8, Rgt(F) = 0.0356, wRref(F2) = 0.1034, T = 100(2) K, β = 90°.